Perception of Medical and Nursing Students and Technical Staff Regarding Telemedicine and Virtual Consultations: Cross-sectional survey in three tertiary care hospitals in India - Khorgade, Chaitanya; Kataria, Vansh; Gurjar, Kiran; Singh, Shakshi; Gupta, Aman; Chaudhary, Vivek; Kumar Garg, Hemant; Singh, Rukmini (Journal of Neonatal Surgery, 2025)
Background: Telemedicine and virtual consultations have expanded rapidly, but perceptions among future and frontline health workers influence adoption and quality. Objective: To assess knowledge, attitudes, perceived preparedness, and barriers toward telemedicine among (a) MBBS students and interns (n=100), (b) nursing students (n=50), and (c) technical staff and nurses (n=100) across three tertiary care hospitals in India. Methods: Cross-sectional descriptive study using a structured questionnaire (demographics, knowledge, attitudes, perceived competence, training needs, and perceived barriers). Data collection planned via paper/online survey. Primary outcomes: proportion with adequate knowledge, positive attitude score, self-reported readiness to participate in teleconsultations. Analysis: descriptive statistics, chi-square, ANOVA/Kruskal–Wallis, and multivariable logistic regression to identify predictors of willingness to adopt telemedicine. Results (illustrative example): (See Results section — simulated data provided as an example template. Actual results require real data collection.) Conclusions: The paper provides a full study protocol, the questionnaire, an analysis plan, proposed tables/figures, and a discussion framework. This can be used as a ready template for data collection, conduct, and manuscript submission